Organic light-emitting diodes comprising highly luminescent red-emitting dendrimers with carbazole-based dendrons. Issue 16 (28th March 2019) - Russell, Steven M.; Brewer, Anthony M.; Stoltzfus, Dani M.; Saghaei, Jaber; Burn, Paul L.
Abstract : OLEDs containing a red emitting dendrimer with a solution PLQY of 86 ± 9% have an EQE of 12% and CIE co-ordinates of (0.65, 0.34). Abstract : Saturated red emitting dendrimers have been prepared for use in organic light-emitting diodes (OLEDs). The dendrimers consist of a homoleptic core iridium(iii ) complex comprising a 2-(thiophen-2-yl)quinoline ligand and fluorenylcarbazolyl-based first generation dendrons with n -propyl surface groups. The dendrimers differ in the position the dendron is attached to the ligand. It was found that the dendrimers had solution photoluminescence quantum yields of up to 86 ± 9%, which is amongst the highest for saturated red phosphorescent emitters. The dendrons and surface groups were found to provide sufficient processing ability to enable good quality films when blended with 4, 4′-bis( N -carbazolyl)-1, 1′-biphenyl (CBP). The dendrimer with the dendron attached to the quinoline unit of the ligand via a phenyl ring was found to have a film PLQY of 87 ± 10% when blended with CBP at a concentration of 10 wt%. A simple two-layer device comprising an emissive layer containing 10 wt% of the dendrimer in CBP and an electron transport layer was found to have a maximum EQE of 12% with CIE co-ordinates of (0.65, 0.34).